Crystal structure of 4-chloro-N′-[(1E)-(2-nitrophenyl)methylidene]benzohydrazide, C14H10ClN3O3 - Al-Wahaibi, Lamya H.; Blacque, Olivier; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter, 2023)
C14H10ClN3O3, triclinic, P1 (no. 1), a = 4.8813(2) Å, b = 6.7806(2) Å, c = 10.3135(2) Å, α = 98.101(2)∘, β = 94.174(2)∘, γ = 97.612(3)∘, V = 333.515(18) Å3, Z = 1, Rgt(F) = 0.0270, wRref (F2) = 0.0743, T = 160 K.